Implications of employees workload in the banking industry: a case of BIMB branches in the central 3 region / Mohd Herry Bahador, Norsaadah Isahak and Nuraini Abd Razak - Bahador, Mohd Herry; Isahak, Norsaadah; Abd Razak, Nuraini (Accounting Research Institute (ARI), UiTM Shah Alam, 2019)
The purpose of this study was to examine the implications of employees’ workload in the banking industry: A case of BIMB branches in Central 3 regions. The ultimate aim of this study was to examine if employees’ workload in BIMB branches in the Central 3 region are influenced by the attributes of stress, job performance and attitudes that has been encountered previously. The outcome suggests that only two attributes significantly give a positive outcome which are attitudes and job performance arising from the implications of workload. A SWOT analysis was used to evaluate internal and external forces and evaluate the benchmark BIMB with industry players such AmBank Islamic, Maybank Islamic and BIMB Branches. The results from the CPM findings indicate that Maybank Islamic had higher scores and were contributed by the reward system and employment loyalty compared to BIMB and AmBank Islamic. Furthermore, it was supported by the Adam’s Equity of Motivation theory to assist Regional Managers of BIMB Branches in the Central 3 region to improvise and enhance the employees-employers exchange to change the employees’ attitudes and improve employee’s performances. The Regional Manager appoints employees who exceed performance from their previous evaluation by giving them a role of authorithy such As coaching new employees on work processes and schedules, inviting them for making decision in managerial roles and organizational conference meetings.